Exploring Commitment to Quality Improvement in State Islamic Senior High Schools: Insights from Aceh - Lensa, Rejeki; Wijaya, Candra; Zein, Achyar (JURNAL AL-TANZIM, 2026)
This study aims to analyze and understand the practice of commitment to improving educational quality in several State Islamic Senior High Schools (Madrasah Aliyah) in Aceh. Using a qualitative, multisite Design, this study examines variations in the implementation of quality assurance across three madrasas with different institutional characteristics. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion. The results indicate that madrasah principals’ commitment is expressed through systematic approaches, relational strategies, and culture-based leadership. Furthermore, quality assurance strategies vary from formal, data-driven systems to flexible, value-based approaches, while stakeholder engagement ranges from structured participation to informal, trust-based collaboration. The implications of this study underscore the importance of tailoring quality improvement strategies to each madrasah's specific context. This research demonstrates that adequate quality assurance requires leadership commitment, tailored strategies, and active stakeholder involvement, all of which contribute to the sustainability of educational improvement. This research provides policymakers and educational leaders with valuable insights for improving the quality of education in madrasahs.